History and Narrative: An Overview - Carrard, Philippe (Narrative Works, 2015)
The articles in this section draw on the texts of plenary lectures presented at the seventh Narrative Matters Conference, Narrative Knowing/Récit et Savoir, organized at the Université Paris Diderot, in partnership with the American University of Paris, from June 23-27, 2014. Philippe Carrard’s article, “History and Narrative: An Overview,” is a sequel to his latest book, Le Passé mis en texte: Poétique de l’historiographie française contemporaine [The Past in Textual Form: A Poetics of Contemporary French Historiography]. In this work, Carrard (2014) sets himself the task of examining, as a scholar of poetics, the writing protocols and conventions used by historians when they finally present the data they have gathered in textual form. One of the major questions of the work concerns to what extent the authors resort to narrative form: does the discourse of the historian always take the form of a narrative and, if not, under what non-narrative forms can it be structured? In the article presented here, Carrard begins by providing an overview of the Anglo-American debate over the cognitive value of narrative in historiography. He opposes this debate, involving mostly analytical philosophers, to the controversies about the relations between narrative and historiography in France, which involve trade historians (starting with the anti-narrativist position of the Annales School). Then he wonders whether literary theory can contribute to these debates. Whereas philosophers and historians raised the question, “Does narrative provide a legitimate kind of knowledge?” literary theorists will simply ask, “Do historians rely on narrative? And if they do, on what kind of narrative?” Answering these questions, of course, includes defining what is meant by “narrative,” something which philosophers and historians, who seem to take the term for granted, often fail to do and which Carrard succeeds in doing, using the works of Gerald Prince, James Phelan, and other theorists of literary narrative. He then shows that a large part of the historians’ production does not fall under narrative, at least not as this term is defined in literary theory, but rather presents itself as what he calls “pictures” (“tableaux”), “analyses,” or “anthropological descriptions.” In his conclusion, he reviews some of the epistemological problems raised by the modes of disposition or arrangement he has described. (Patron & Schiff, 2015)